CARA PEMUTAKHIRAN DATA DAFTAR PEMILIH TETAP PEMILU KEPALA DAERAHWAKIL KEPALA DAERAH BERDASARKAN PERATURAN KPU NOMOR 09 TAHUN 2010 - Indra Muda (PERSPEKTIF, 2012)
Refers to the goal of Regional Head / Vice Regional Head which is to obtain local leaders who really pay attention to the people’s aspirations so that the people feel their aspirations considered by the leaders they choose. To know the leader that will be chosen by the people, KPU do the crawl towards the candidates based on the determined steps. The problems of this research are whether the determintaion of North Sumatera Region Head / Vice Regional Head General Election’s voters register is appropriate with the fixed regulation, and whether North Sumatera KPU finds obstacles to determine the accurate voters register. Based on the experience of the implementation of North Sumatera Region Head / Vice Regional Head at the last period, the voters register (DPT) determintaion has been done according to PP No. 17 Year 2005 and PP no. 25 year 2007. For the next General Election, to avoid the double voters in the voters register the DP Tools system will be done, by using the detection at the computer, if it is found the double voters then automatically one of them will be deleted. North Sumatera people is a compound people which is not easily provoked by the negative issues, although some riot happens in some region in Indonesia for the implementation of the regional Head General Election, then vice versa in Noeth Sumatera, the election process at some TPS runs smoothly without any obstacle. Regional Head and Vice Regional Head General Election on 2008 was successfully won by Saymsul Arifin, SE and Ir. Gatot Pujo Nugroho.